A noção de infinito em livros didáticos do ensino básico - Lopes, Silvio Joaquim (2011)
This work focuses on lifting the approach of the notion of infinity in textbooks that refer to the school term which comprises from the Early Education to High School Education. It refers, therefore, to the analysis of textbooks. To collect data we used the assumptions of Content Analysis having as an aim the verification of the situations presented in the books analysed and consequently the concepts covered in them, evidence or clue of the notion of infinity. In this work you will also be able to see a historical survey of the development of notion of infinity as well as a bibliography of researches focusing on the teaching and the learning of this notion. For the theoretical foundation, we choose the Conceptual Fields Theory of Gerard Vergnaud because of the multiplicity of situations they involve and that define the notion of infinity. With this study we can observe signs and approach of clues of the notion of infinity us investigated books in the different levels of Basic Education. We understand that the explanation of these clues can contribute to help its possible use made by teachers and researchers